A pathway to 'constant becoming': time, temporalities and the construction of self among South Korean educational migrants in Singapore. Issue 5 (3rd September 2018) - Kang, Yoonhee
ABSTRACT: This study explores the significance and complexity of time practices and experiences in understanding the emerging identities and aspirations of South Korean pre-college students and their mothers who moved to Singapore for the children's education. I adopt the notion of chronotope, a spatial-temporal frame for a specific type of personhood, to analyze (1) the discrepant experiences of time and temporalities between Korean students and their accompanying mothers, and (2) the intersections between the Korean migrants' subjective experiences of time and their imaginings of social positioning in transnational contexts. The Korean students' identities were often imagined and constituted through a chronotope of 'constant becoming' oriented toward the future and the global, while their mothers typically conceptualized and expressed their migration experiences as a confined time of 'intensive mothering', reflecting a chronotope of traditional mothering that often belongs to pre-modern time and space. Thus, revealing the chronotopes of the different generations promotes understanding of their shifting identities as articulated through multiple scales of time and space, mediating between the present and the future, and the local and the global.